2022
DOI: 10.1097/mog.0000000000000864
|View full text |Cite
|
Sign up to set email alerts
|

The spectrum of diabetes in acute and chronic pancreatitis

Abstract: Purpose of reviewTo discuss the spectrum of diabetes related to acute and chronic pancreatitis (which are types of pancreatogenic diabetes) and its overlapping features with type 1 and type 2 diabetes.Recent findingsPatients with diabetes related to acute and chronic pancreatitis present clinically within a spectrum of overlapping features with other forms of diabetes. In this spectrum, glucose metabolism alterations range from increased insulin resistance following acute pancreatitis (resembling type 2 diabet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…The progressive nature of DEP, especially associated with advanced chronic pancreatitis, often warrants treatment intensification, such that many patients initially controlled with metformin may ultimately require insulin once insulin deficiency develops. For example, a patient with PPDM-A who goes on to develop recurrent acute or chronic pancreatitis may also experience worsening glucose tolerance, necessitating changes in their antidiabetic regimen [ 17 ]. In a case series of 38 patients with DEP (6 associated with pancreatic cancer and 32 with benign pancreatic disease), metformin alone was the most common initial treatment, but 30 of the 38 patients required insulin within 12 months of diagnosis [ 18 ].…”
Section: Key Pharmacological Management Considerationsmentioning
confidence: 99%
“…The progressive nature of DEP, especially associated with advanced chronic pancreatitis, often warrants treatment intensification, such that many patients initially controlled with metformin may ultimately require insulin once insulin deficiency develops. For example, a patient with PPDM-A who goes on to develop recurrent acute or chronic pancreatitis may also experience worsening glucose tolerance, necessitating changes in their antidiabetic regimen [ 17 ]. In a case series of 38 patients with DEP (6 associated with pancreatic cancer and 32 with benign pancreatic disease), metformin alone was the most common initial treatment, but 30 of the 38 patients required insulin within 12 months of diagnosis [ 18 ].…”
Section: Key Pharmacological Management Considerationsmentioning
confidence: 99%
“…The American Diabetes Association classifies CP‐related diabetes as type 3c diabetes, which shares many similarities with T2D in terms of clinical presentation and treatment 9 . According to a spectrum analysis of diabetes, in addition to the pathophysiological mechanisms associated with CP, many patients with CP‐related diabetes also have risk factors associated with T2D 10 . Another study showed that the combination of CP and T2D can lead to a mutually aggravating process involving insulin resistance, chronic low‐intensity inflammation, and dyslipidemia 11 .…”
Section: Introductionmentioning
confidence: 99%
“… 9 According to a spectrum analysis of diabetes, in addition to the pathophysiological mechanisms associated with CP, many patients with CP‐related diabetes also have risk factors associated with T2D. 10 Another study showed that the combination of CP and T2D can lead to a mutually aggravating process involving insulin resistance, chronic low‐intensity inflammation, and dyslipidemia. 11 Moreover, compared to comorbidity in CP‐T2D, patients with diabetes related to CP present a more aggressive phenotype (microangiopathy and infection) and higher need for glucose‐lowering treatment, and even patients who experience their first attack of pancreatitis may require long‐term management after being discharged from the hospital.…”
Section: Introductionmentioning
confidence: 99%
“…However, treatment response in these patients has not been systematically assessed. Type 3c diabetes is a very heterogenous condition, [7,17] and therefore the different underlying causes could also potentially result in different treatment responses. In addition to the endocrine dysfunction that results in diabetes, the exocrine functions of the pancreas can be damaged resulting in pancreatic exocrine insufficiency (PEI).…”
Section: Introductionmentioning
confidence: 99%